MENCIPTAKAN SCIENTIST CILIK MELALUI PEMBELAJARAN SAINS - Dwi Prasetyawati Dyah H (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2011)
Science subject is one of learning that make children to explore the natural phenomena through direct interaction with the object. The introduction of science to children kindergarten / early childhood if done properly will gradually develop the ability to think logically that does not yet have children. The thing to do when learning science educators are educators need to invite children to make the process of observing and suspect. Both of them are related, but have a difference of principle. Observing is the process of using all the senses of children to gather data about an object or phenomenon. Observing is an active process, not just passively seeing something happening. Observing the basic skills in it contains the elements of thought (inferring), measuring (measuring), and communicating (communicating). Suspect is collecting opinions or estimates based on the evidence. Allegations will develop hypotheses, interpreting data and identify patterns, common things that might happen, and a certain tendency. From the patterns, generalizations and trends of the early childhood to make sense of the world.